Analisis Kinerja Distribusi dan Bottleneck Operasional pada Rantai Pasok Usaha Barang Bekas: Studi Kasus UD. DOA ABADI, Semarang - Fajriansyah Mahdy Tsani; Rifki Navis Haidar (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
The trade of used goods is a vital component of the circular economy, as it extends the material lifecycle through collection, sorting, storage, and redistribution activities. However, the uncertain and heterogeneous nature of the supply creates supply chain management challenges, particularly regarding distribution performance. This study aims to evaluate the distribution performance of the supply chain system at UD. DOA ABADI, a used-goods trading business in Semarang City dealing in commodities such as scrap iron, cardboard, paper, and plastic bottles. A descriptive quantitative approach with a single case study design was employed, utilizing operational data from June 2025 to June 2026. The analysis utilized an inventory mass balance model and distribution performance indicators—specifically inflow-outflow balance, warehouse utilization, and inventory turnover—alongside an operational capacity bottleneck analysis and an evaluation based on the Supply Chain Operations Reference (SCOR) model. The results indicate that the company's distribution capacity has not fully kept pace with the supply rate, resulting in gradual stock accumulation, increased warehouse utilization, and slower inventory turnover. Bottleneck analysis identified the distribution fleet as the primary operational constraint, as it operates near maximum capacity limits; meanwhile, external factors—specifically the vulnerability to tidal flooding in the North Semarang coastal area—pose a risk of further exacerbating distribution disruptions. This study demonstrates that combining simple operational indicators with the SCOR model is effective for evaluating distribution performance in informal, circular economy-based businesses and provides a foundation for recommendations to improve distribution efficiency within the micro-scale used-goods trading sector